HIV-associated depression: a translational framework targeting neuroimmune inflammation and psychosocial stress modulation - Yu, Fei; Zhu, Yue; Fan, Yiran; Chen, Mingqi; Peng, Qing; Li, Shenghao; Hao, Liyuan; Ye, Fanghang; Xia, Jiajun; Hu, Xiaoyu (Frontiers in Immunology, 2025)
People living with HIV (PLWH) are at increased risk for depression, anxiety, and other comorbid psychiatric disorders. HIV-associated depression involves complex neurobiological disturbances, including chronic neuroinflammation. This includes microglial activation, elevated levels of pro-inflammatory cytokines and mediators, and altered brain metabolites. Additionally, there is dysregulation of monoaminergic neurotransmission, particularly impaired serotonergic signaling. Prolonged hyperactivation of the hypothalamic-pituitary-adrenal axis, indicated by abnormally high cortisol levels, is also observed. Together, these pathological processes contribute to persistent brain inflammation and metabolic imbalance. Under prolonged inflammatory conditions, activated microglia release factors such as tumor necrosis factor-alpha. These factors can induce oligodendrocyte apoptosis and demyelination, exacerbating neural injury. Psychosocial stressors—such as stigma, death-related anxiety, and internalized shame—may amplify these pathways through immune-neural crosstalk. Our primary focus, however, is on pharmacological targeting. We propose a three-tiered intervention framework: 1) Targeted neuropharmacological interventions (e.g., SSRIs and anti-inflammatory agents); 2) Optimized ART regimens; 3) Integrated psychosocial support. While further research is needed to establish long-term efficacy and personalized treatment options, this multidimensional approach may reduce the progression of HIV-associated depression and improve clinical outcomes.